Lung Function and Asthma Clinical Control in N-ERD Patients, Three-Year Follow-Up in the Context of Real-World Evidence - Pavón-Romero GF; Falfán-Valencia R; Gutiérrez-Quiroz KV; De La O-Espinoza EA; Serrano-Pérez NH; Ramírez-Jiménez F; Teran LM (Journal of Asthma and Allergy, 2023)
Gandhi Fernando Pavón-Romero,1 Ramcés Falfán-Valencia,2 Katia Vanessa Gutiérrez-Quiroz,1 Estivaliz Arizel De La O-Espinoza,1 Nancy Haydée Serrano-Pérez,1 Fernando Ramírez-Jiménez,1 Luis M Teran1 1Department of Immunogenetics and Allergy, Instituto Nacional de Enfermedades Respiratorias, Mexico City, Mexico; 2Laboratory of Human Leukocyte Antigen, Instituto Nacional de Enfermedades Respiratorias, Mexico City, MexicoCorrespondence: Luis M Teran, Department of Immunogenetics and Allergy, Instituto Nacional de Enfermedades Respiratorias, Ismael Cosío Villegas, Tlalpan, Mexico City, 14080, Mexico, Tel +52 5557481700 exr. 5162, Email teranjlm@gmail.comPurpose: To describe the lung function and clinical control of asthma in patients with N-ERD during three years of medical follow-up using GINA guidelines.Methods: We evaluated 75 N-ERD and 68 asthma patients (AG). Clinical control, lung function, and asthma treatment were evaluated according to GINA-2014. We compared all variables at baseline and one, two, and three years after treatment.Results: At baseline, the N-ERD group had better basal lung function (LF) than the AG group (p< 0.01), and the AG group used higher doses of inhaled corticosteroids than the N-ERD group (52.4% vs 30.5%, p=0.01) and short-term oral corticosteroid (OCS) use (52.4% vs 30.5%, p< 0.01). Instead, N-ERD patients needed more use of leukotriene receptor antagonists (LTRA) (29.3% vs 5.9%, p< 0.01). This group had better clinical control than the AG group (62.1% vs 34.1%, p< 0.01). During the medical follow-up, the LF of the N-ERD group remained at normal values; however, these parameters improved in AG from one year (p< 0.01). Likewise, there was a diminished use of high doses of ICS (52.4% vs 33%, p< 0.05) and short-term OCS (67.6% vs 20.6%, p< 0.01) in asthma patients. However, N-ERD patients still needed more use of LTRAs (p< 0.02) during the study. In this context, one-third of N-ERD patients had to use a combination of two drugs to maintain this control. From the second year on, clinical control of asthma was similar in both groups (p> 0.05).Conclusion: According to GINA guidelines, only one-third of patients with N-ERD can gradually achieve adequate lung function and good asthma control with a high ICS dosage. Only a very small portion of patients will require the continued use of a second medication as an LTRA to keep their asthma under control.Keywords: N-ERD, asthma, severe asthma, corticosteroids, GINA guidelines, asthma clinical control